2020 IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC) 2020
DOI: 10.1109/nss/mic42677.2020.9507859
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Radiotherapy Dose Fields from a Few Projections: How Many Projections will Ensure Uniqueness?

Abstract: The cross-section of the dose field generated by a linac with multi-leaf collimators (MLC) can be examined using scintillating fiber technology to obtain a few parallel projections of this (nearly) binary image. We examine ambiguity of the reconstructions when using only six projections, and demonstrate that unique solutions cannot be ensured. We suggest alternative approaches or conditions on the MLC configuration that would restore unicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…However, these differences remain in all cases submillimeter, which is acceptable. It is also noted that the proposed 2D dose reconstruction method can be extended to more complex shapes defined by the MLC 33 (by using the a priori knowledge of the leaves geometry).…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences remain in all cases submillimeter, which is acceptable. It is also noted that the proposed 2D dose reconstruction method can be extended to more complex shapes defined by the MLC 33 (by using the a priori knowledge of the leaves geometry).…”
Section: Discussionmentioning
confidence: 99%
“…multiple global minima). For 6 projections, non-uniqueness has been demonstrated for as few as N = 32 leaf-pairs (Pivot et al 2020). Increasing the number of measured projections would be required for handling more pairs of leaves.…”
Section: Reconstruction Algorithmmentioning
confidence: 99%
“…the measurements correspond to one unique MLC irradiation field). It has been demonstrated that even for binary objects, uniqueness cannot be ensured but most of the non-unique situations can be avoided by using a detector with enough projection angles (Pivot et al 2020). For six projections, non-uniqueness situations can arise with 32 or more leaf-pairs.…”
Section: Introductionmentioning
confidence: 99%